Genomic organization of the 5′ region of the human thyroglobulin gene - Moya, C. M. (2000)
Objective: The purpose of the present work is to establish the intron - exon organization from exon 12 to exon 23 of the human thyroglobulin gene and to construct a physical map of the 5′ terminal half of the gene. Design: Screening of a genomic library and subsequent restriction map, hybridization and sequencing methods have been employed to characterize the recombinant positive phages. Methods: A human genomic DNA library was screened by in situ hybridization. Southern blotting experiments were performed to characterize the phage inserts. Intron/exon junction sequences were determined by the Taq polymerase-based chain terminator method. Finally, the thyroglobulin gene was mapped using the Gene Bridge 4 radiation hybrid clone panel. Results: We isolated and characterized four λ phage clones that include nucleotides 3002 to 4816 of the thyroglobulin mRNA, encompassing exons 12 to 23 of the gene. The exon sizes range between 78 and 219 nucleotides. We found that the GT-AG splicing sequences rule was perfectly respected in all the introns. A total of 7302 intronic bases was analyzed. Hormogenic tyrosine 5 and 1291 are encoded by exons 2 and 18. Also, seven alternative spliced variants are associated with the 5′ region. Thyroglobulin gene maps to 5.5 centiRays from the AFMAO53XF1 marker, in chromosome 8. Conclusions: The present study shows that the first 4857 bases of thyroglobulin mRNA are divided into 23 exons and the four phages isolated include 32.6 kb genomic DNA, covering 1815 nucleotides of exonic sequence distributed in 12 exons, from exon 12 to 23.